2021
DOI: 10.1177/24741264211039960
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Demographic Factors Contributing to COVID-19–Related Delays and Reductions in Primary Retinal Detachment Repair in a US Hot Spot

Abstract: Purpose: This work evaluates demographic and socioeconomic predictors of delayed care for rhegmatogenous retinal detachments (RRDs) during the spring 2020 COVID-19 shutdown in a US hot spot. Methods: This multicenter, retrospective, case-control study took place in 3 academic vitreoretinal practices in metropolitan Boston. Consecutive patients treated for RRD during the COVID-19 state of emergency were compared with patients treated during the same period in 2018 and 2019. The primary outcome was macula status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…One study demonstrated that low-income, government-sponsored health insurance was a predictor of macula-off RRD status during the 2020 COVID-19 pandemic. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that low-income, government-sponsored health insurance was a predictor of macula-off RRD status during the 2020 COVID-19 pandemic. 13…”
Section: Discussionmentioning
confidence: 99%
“…Saraf et al 8 reported a higher prevalence of RRD among Whites compared with other races using the Intelligent Research in Sight Registry. Port et al 13 reported that non-Hispanic White race/ethnicity and those with income-level Medicaid or MassHealth (a state-sponsored insurance program for low income) were associated with deferral of care during the 2020 COVID-19 pandemic, resulting in more macula-off RRDs and significantly longer duration of symptoms. We found that Hispanics had the highest RRD ED incidence and Native Americans had the lowest.…”
Section: Discussionmentioning
confidence: 99%